Pharmacological criteria that can affect the detection of doping agents in hair - Kintz, P.; Cirimele, V.; Ludes, B. (Forensic Science International, 2000)
When positive drug results are reported, a common interpretive question posed is whether or not it is possible to put a quantitative finding into context. A standard answer to this inquiry is that a positive hair testing result can be interpreted as meaning that the donor has chronically or repetitively used the drug identified in the hair, but that chronic or repetitive are not defined in the same way for all individuals. The Society of Hair Testing published on June 16, 1999, a consensus opinion on the use of hair in doping situations. However, although accepted in most courts of justice, hair analysis is not yet recognised by the International Olympic Committee. To be considered as a valid specimen for doping control, some issues still need to be addressed. The scientific community has demonstrated significant concern over the proper role that hair drug testing should serve in toxicological applications. Among the unanswered questions, five are of critical importance: (1) What is the minimal amount of drug detectable in hair after administration? (2) What is the relationship between the amount of the drug used and the concentration of the drug or its metabolites in hair? (3) What is the influence of hair color? (4) Is there any racial bias in hair testing? (5) What is the influence of cosmetic treatments? The present report documents scientific findings on these questions, with particular attention to the applications of hair in doping control.